Trade with Chinese characteristics - economics versus politics - Eeva Kerola; Tuuli McCully; Riikka Nuutilainen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
Over the past twenty years, China has become the world's largest trading nation and a significant trading partner for most countries. Despite these important links, concerns regarding China's commercial and diplomatic goals persist due to its unique state-centric economic structure. This paper applies an augmented gravity model to tease out drivers of China's bilateral trade relationships, asking why some countries are more important than others as sources of Chinese imports. Our results show that both business and political considerations drive China's import decisions. Political friendliness with China, as measured by UN General Assembly voting records, or established trade agreements, has a positive impact on exports to China. The results further suggest that countries with official diplomatic ties with Taiwan export less to China. Membership in China's Belt and Road Initiative, however, does not generally translate into a significant increase in Chinese imports from the member country.
urn:nbn:fi-fe2024091170372
Keywords: C23; F14; F15; 330; gravity model; international trade; China